2011
DOI: 10.1371/journal.pone.0022586
|View full text |Cite
|
Sign up to set email alerts
|

Expression and Rhythmic Modulation of Circulating MicroRNAs Targeting the Clock Gene Bmal1 in Mice

Abstract: MicroRNAs (miRNAs) interact with 3′ untranslated region (UTR) elements of target genes to regulate mRNA stability or translation and thus play a role in regulating many different biological processes, including circadian rhythms. However, specific miRNAs mediating the regulation of essential clock genes remain largely unknown. Because vesicles containing membrane-bound miRNAs are present in the circulatory system, we examined miRNAs predicted to target the clock gene, Bmal1, for evidence of rhythmic fluctuatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
76
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(81 citation statements)
references
References 55 publications
3
76
0
Order By: Relevance
“…We discovered that miRNA levels varied significantly with the blood sampling time, and all three miRNAs studied had lower levels in the blood samples taken in the evening, suggesting a possible impact of the circadian rhythm on miR-200 levels. Recent publications have already provided evidence that miRNAs are involved in the regulation of the circadian rhythm and, more importantly, that the level of some miRNAs is probably regulated by the circadian clock (37,38). Bioinformatics tools were used to predict miRNAs presenting putative sites for circadian transcription factors in their promoters, and the diurnal variation of miR-27b in human leukocytes was experimentally validated (37).…”
Section: Discussionmentioning
confidence: 99%
“…We discovered that miRNA levels varied significantly with the blood sampling time, and all three miRNAs studied had lower levels in the blood samples taken in the evening, suggesting a possible impact of the circadian rhythm on miR-200 levels. Recent publications have already provided evidence that miRNAs are involved in the regulation of the circadian rhythm and, more importantly, that the level of some miRNAs is probably regulated by the circadian clock (37,38). Bioinformatics tools were used to predict miRNAs presenting putative sites for circadian transcription factors in their promoters, and the diurnal variation of miR-27b in human leukocytes was experimentally validated (37).…”
Section: Discussionmentioning
confidence: 99%
“…In the present investigation of the plasma miRNA profiles of smokers and non-smokers, the subjects were limited to men because a study had reported subtle sex differences (Ji et al, 2009), although another study reported no large sex differences in plasma miRNA expression (Chen et al, 2008), and because smoking is more prevalent in men than in women in Japan. In addition, considering the potential effects of circadian rhythm (Shende et al, 2011), we standardized the time of blood collection.…”
Section: Discussionmentioning
confidence: 99%
“…MicroRNAs were not only detected in cells, but also in exosomes. In fact, miR-152 and miR-494 have been shown to exhibit circadian rhythms in the serum [102]. This finding indicates that that the exchange of circadian information between cells and within the multioscillator system is not restricted to hormones and neurotransmitters, but also involves microRNAs released as exosomes into the blood and, presumably, other body fluids.…”
Section: Resultsmentioning
confidence: 97%